Accelerated radiotherapy for T1 to T2 glottic cancer. Issue 4 (10th April 2014) - Motegi, Atsushi; Kawashima, Mitsuhiko; Arahira, Satoko; Zenda, Sadamoto; Toshima, Masamichi; Onozawa, Masakatsu; Hayashi, Ryuichi; Akimoto, Tetsuo
Abstract: Background: Accelerated fractionation radiotherapy (RT) was administered in an attempt to improve the local control rates in patients with T1/T2 N0 glottic cancer. Methods: Medical charts of 148 consecutive patients who had undergone RT using 2.4 Gray (Gy) once‐daily fractionation between July 1999 and April 2007 were reviewed. Results: Of 104 patients with T1 disease treated by RT, 82 received 60 Gy/25 fractions, and the remaining 22 with large tumor volumes and/or slow response to RT received 64.8 Gy/27 fractions. All 44 patients with T2 disease received 64.8 Gy/27 fractions. The 5‐year local control and overall survival (OS) rates were 93% and 96%, respectively, in patients with T1 disease, and 77% and 91%, respectively, in patients with T2 disease. No severe acute toxicities were observed, although 2 patients (1%) developed severe late toxicity. Conclusion: Accelerated RT for early glottic cancer is feasible, with encouraging local control rates. © 2014 Wiley Periodicals, Inc. Head Neck 37 : 579–584, 2015